Case reports of rhino-orbital mucor mycosis following dengue and typhoid, from a tertiary care institute - Tiwari, Rajesh; Tomar, Akanksha; Soni, Rupesh (International Journal Of Community Medicine And Public Health, 2022)
Mucor mycosis is a highly invasive and progressive opportunistic infection with higher rates of morbidity and mortality. It is attributed to compromised immunity status of individuals with poor oral and nasal hygiene. It got rapidly progressed and become a visible threat to the life among the delayed diagnosed cases. Therefore, new threats and pathogenesis are required to understand the prevention and treatment of the disease. Dengue is the most common arthropod born viral disease but unfortunately no effective antiviral treatment is available till now. Two case reports were done to illustrates the pathway of Mucor mycosis in dengue and typhoid infection, admitted at Tertiary Care hospital of Jabalpur District. Data was collected through interview with the case and care taker and case file review. These were the case of rhino- orbital Mucor mycosis attributed to compromised immunity during the treatment of respective infection. The early diagnosis, prompt Treatment with necessary surgical intervention are the essential steps to slow down the disease progression as well as successful outcome.